THE IMPACT OF SERVICE QUALITY AND PRICE TO CUSTOMER SATISFACTION AND CUSTOMER LOYALTY IN SWISS-BELHOTEL MALEOSAN MANADO - Montolalu, Marcelitha T. (Universitas Sam Ratulangi, 2013)
Loyalty of the firm's customers has been recognized as the dominant factors in a business organization's success.Â Service quality and price are vital competitive policy to keep customer support and build great base. Hotels are trying to win customer loyalty by providing good quality services, affordable price and also make sure that customers are satisfied. This study is aimed to analyze the influence of service quality and price to customer satisfaction, service quality and price to customer loyalty and customer satisfaction to customer loyalty. This study is conducted in Swiss-Belhotel Maleosan Manado with 99 respondents. This study uses Path Analysis Method and also includes validity test, reliability test, and classical assumption. The results of the study indicate that service quality and price has a positive significant influence to customer satisfaction; service quality and price has a positive significant influence to customer loyalty; and customer satisfaction has positive significant influence to customer loyalty. Keywords: service quality, Â price, customer satisfaction, customer loyalty